Sosialisasi Penguatan Perilaku Hidup Bersih Dan Sehat Bagi Masyarakat Di Desa Jagoi: Socialization Of Strengthening Clean And Healthy Living Behavior For The Community in Jagoi Village - Musa, Dahniar Th; Marbun, Posmanto; Annisa Rizqa Alamri; Mutmainnah (Sam Ratulangi University, 2024)
The educational result of understanding a set of behaviours practised is clean and healthy living behaviour. The purpose of this Community Service (PkM) activity is to arouse and increase public understanding, especially housewives, of the importance of implementing clean and healthy living behaviour in various order, namely workplaces, educational institutions, homes, health facilities, and public places. This PkM activity is carried out using the socialization and counselling method with several stages of implementation. The socialization and counselling method is the right method because the number of participants is 30 (thirty) people consisting of: the head of the PKK driving team and members, hamlet heads, village heads, religious leaders, community leaders, young people, and law enforcers so that it is carried out with lectures interspersed with question and answer sessions. In addition, this activity is also carried out by forming a Focus Group Discussion (FGD) in order to unite the views of the Jagoi Village community regarding the material provided, namely clean and healthy living behaviour. As a result, the insight of the Jagoi Village residents regarding clean living behaviour has increased and there are actions and changes in behaviour towards a better direction. ABSTRAK Hasil edukasi dari pemahaman seperangkat perilaku yang dipraktikkan adalah perilaku hidup bersih dan sehat. Maksud kegiatan Pengabdian kepada Masyarakat (PkM) ini yaitu untuk menggugah serta meningkatkan pemahaman masyarakat khususnya para ibu rumah tangga akan pentingnya implementasi berperilaku hidup bersih dan sehat di berbagai tatanan yaitu tempat kerja, lembaga pendidikan, rumah tinggal, fasilitas kesehatan, dan tempat publik. Kegiatan PkM ini dilaksanakan dengan metode sosialisasi dan penyuluhan dengan beberapa tahapan pelaksanaan. Metode sosialisasi dan penyuluhan merupakan metode yang tepat karena jumlah peserta sebanyak 30 (tiga puluh) orang terdiri dari dari: ketua tim penggerak PKK dan anggota, kepala dusun, kepala desa, pemuka agama, para tokoh masyarakat, kaum muda, dan penegak hukum sehingga dilakukan dengan ceramah diselingi dengan sesi tanya jawab. Selain itu, dalam kegiatan ini juga dilakukan dengan membentuk Focus Group Discussion (FGD) agar dapat menyatukan pandangan masyarakat Desa Jagoi tentang materi yang diberikan yakni perilaku hidup bersih dan sehat. Hasilnya, wawasan penduduk Desa Jagoi berkenaan perilaku hidup bersih semakin meningkat serta terdapatnya tindakan dan perubahan perilaku menuju arah yang lebih baik.